Drama and the Sacraments in Sixteenth-Century England - Coleman, D. author. aut Link
VIII, 180 p.
Keywords: This is the first book-length study of the relationship between early modern drama and sacramental ritual and theology. It examines dramatic forms, such as morality plays. Offering new insights into the religious practices on which early modern subjectivity is founded. Coleman offers radical new ways of reading canonical Renaissance plays.